Features of the marketing activities of the rugby club "Olympus" Kharkiv - Svitlana Stadnyk (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the features of the marketing activities of the "Olympus" rugby club for its further improvement. Material and methods: using PEST-analysis, the influence of the external environment on the activities of the "Olympus" rugby club was characterized. Using SWOT-analysis, the opportunities and threats of the external environment and the strengths and weaknesses of the internal environment of the "Olympus" rugby club were identified. The survey was conducted among 10 organizational and managerial staff of the rugby club "Olympus" Kharkiv in order to determine the opinion of respondents regarding various aspects of its activities, as well as among 25 club rugby athletes in order to identify needs and priorities, motivate team players. Results: substantiate the need for a marketing strategy, the development process of which in our study included 3 stages: analysis of the external and internal environment of the club; formation of goals, main directions and marketing complex; implementation and evaluation of marketing strategies. The organizational structure of the "Olympus" rugby club, its logo, and an analysis of the club's marketing communications are analyzed. Conclusions: as a result of the study, we developed a marketing strategy for the "Olympus" rugby club and a plan for its practical implementation. The results of the expert evaluation indicate that the marketing strategy we have proposed has the high expected effectiveness, scientifically justified, and real for implementation.